Agreement of results between dry and wet chemistry system for common clinical chemistry parameters - Saroj Thapa; Apeksha Niraula; Prabodh Risal (Journal of Pathology of Nepal)
Background: The advancement of analytical chemistry has led to the use of automated systems in clinical laboratories, including liquid-based wet chemistry and film-based dry chemistry systems. Reflectance spectrophotometry-based dry chemistry systems offer a viable alternative to wet chemistry analyzers. This study aimed to compare the agreement of results between the dry chemistry system and the wet chemistry system.